Comparison of Myeloid Cells in Circulation and in the Tumor Microenvironment of Patients with Colorectal and Breast Cancers - Salman M. Toor; Eyad Elkord (Journal of Immunology Research)
We have previously reported levels of myeloid cells in the periphery and in the tumor microenvironment (TME) of patients with primary breast cancer (PBC) and colorectal cancer (CRC). We found that both PBC and CRC patients have significantly higher levels of granulocytic and immature myeloid cells in the TME. Additionally, we reported an expansion of circulating granulocytic myeloid cells in CRC patients, but not in PBC patients. In this report, we compared levels of myeloid cells between these two common cancers and have added data from more cancer patients. We also investigated associations between clinical stage/histological grade of tumors and levels of myeloid cells in cancer patients. We found that although granulocytic myeloid cells were expanded in the TME of both PBC and CRC patients, the levels of these cells were significantly higher in the TME of CRC patients. Moreover, our results indicate that increased levels of circulating granulocytic myeloid cells are associated with poorly differentiated tumors in CRC patients. Taken together, this work suggests that CRC patients may benefit more from the development of therapeutic agents to promote myeloid cell differentiation or inhibition for the reversal of immune suppression.